Minimum Wage vs Inflation in Poland and Czechia in 2004-2024 - Kampa, Marta; Maciejasz, Marta (Publishing House of Wroclaw University of Economics and Business, 2025)
This study aimed to assess the relationship between changes in the minimum wage and inflation in Poland and Czechia between 2004 and 2024. The research question was: is there a relationship between inflation and the minimum wage in the selected countries? It was assumed that changes in the minimum wage and inflation are unidirectional, meaning that increases in inflation are associated with increases in the minimum wage. However, the strength and nature of this relationship may vary across countries, due to factors including differences in the socioeconomic policies pursued by individual countries. The study employed a case study approach for selected countries and correlation analysis, using statistical data from 2004 to 2024. Calculation of the correlation coefficient between the annual inflation rate (HICP) and the minimum wage allowed for an assessment of the strength and direction of the relationship between these variables. The results confirmed the existence of a positive correlation in both countries, where the strength of the relationship was medium, and changes in the minimum wage were often delayed and driven by political decisions.
Quote as: Kampa, M., & Maciejasz, M. (2025). Minimum Wage vs Inflation in Poland and Czechia in 2004-‑2024. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 91-103). Publishing House of Wroclaw University of Economics and Business.
Keywords: inflation; minimum wage; Poland; Czechia